Innovative Approaches to Financial Distress: The Impact of Company Size and Sales Growth on Food and Beverage Companies Listed on the Indonesia Stock Exchange - Yayu Kusdiana; Ramadahniel Islami; Nanda Suryadi (Yayasan Pendidikan Islam Al-Matani, 2025)
This study aims to examine the direct effects of company size and sales growth on financial distress in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The research adopts a quantitative approach, utilizing a sample of 235 observations drawn from a population of 84 companies within the food and beverage subsector. Secondary data from publicly available reports from the IDX was used for this analysis. The data were analyzed using the SmartPLS 3.0 model. The results indicate that company size does not significantly influence financial distress, and similarly, sales growth does not have a significant impact on financial distress.